Homeowner investor subjects as providers of family care and assistance. Issue 6 (3rd July 2019) - Nethercote, Megan
Abstract: This article asks: What becomes of the idealized asset-accumulating investor subject rallied in asset-based welfare policy and discourse in the context of mounting social risks facing families? It brings into dialogue two disconnected literatures: one on financialized subjectivities, drawing on post-structuralist and Foucauldian analysis, the other on welfare states drawing more heavily on comparative political economy. Drawing on homeowner interviews in Melbourne (Australia), it identifies how parent homeowners' devise housing strategies to manage their children's housing welfare risks. Their housing investment and landlordism strategies align with financialized subjectivities, but other strategies subvert or reject these subject positions. Its first contribution is to specify how an Australian refamilization of welfare responsibilities, including for housing, is unfolding as processes of financialization erode the efficacy of growing state social spending. Its second contribution is to challenge the individual subject of asset-based welfare (ABW) and introduce intergenerational assistance as an under-explored contingency for ABW projects, and further driver for welfare inequalities between and within generations.